DETERMINANTS OF OUTCOME OF MODERATE TO SEVERE COVID-19 IN A HOSPITAL SETTING: A COMPARISON BETWEEN FIRST AND SECOND/THIRD WAVE IN LOMBARDY. (June 2022) - Boari, Gianluca; Leidi, Francesca; Accordini, Beatrice; Napoli, Federico; Ghidelli, Chiara; Archenti, Giulia; Chiarini, Giulia; Malerba, Paolo; Scarano, Ottavio; Mangili, Benedetta; Gorla, Giulia; Corbani, Andrea; et al.
Abstract : Objective: Coronavirus disease 2019 (COVID-19) represents a major clinical problem in terms of death and long-term sequelae. We conducted a retrospective cohort study at Montichiari Hospital (Brescia, Italy) to better understand different determinants of outcome in different COVID-19 outbreaks. Design and method: A total of 635 patients admitted from local emergency room with a confirmed diagnosis of SARS-CoV-2 infection and a moderate to severe COVID-19 were included in the present study. A group of 260 consecutive patients during SARS-CoV-2 first wave (from February to May 2020) and 375 consecutive patients during SARS-CoV-2 second/third wave (from October 2020 to May 2021) were considered. Demographic data, comorbidities, ongoing treatment and bio-humoral, respiratory and haemodynamic data were recorded and compared. Results: Main demographic data (Table 1) were not significantly different in the two considered time-lapses, except a lower prevalence of female sex during first wave. Mortality rate was significantly lower during the latter period (25% vs 11%; p < 0.001). Time from symptoms onset to hospital admission was longer during first wave (7.8 ± 5.6 vs 5.6 ± 4.3 days; p < 0.001) while hospital staying was significantly shorter (11 ± 10 vs 15 ± 12 days; p < 0.001). Other significant differences were a wider use of corticosteroids and low-molecular weight heparin (LMWH) as well less antibiotic prescription during the second wave (Table 2). Respiratory, bio-humoral and x-Ray score were significantly poorer at the time of admission in first-wave patients (Table 3). After a multivariate regression analysis, C-reactive protein and procalcitonin values, % fraction of inspired oxygen at admission, days after symptoms onset and duration of hospital staying were the strongest predictors of outcome in both periods. Concomitant anti-hypertensive treatment (including ACE-inhibitors and ARBs) did not affect outcome. Conclusions: Our preliminary data suggest that an earlier diagnosis, a timely hospital admission and a rational use of the therapeutic options allowed to reduce the rate of systemic inflammation response (of which CRP is a hallmark) and granted a better outcome during the second of the two time-lapses considered.